Lab on a Chip – past, present, and future. Issue 7 (25th March 2021) - Manz, Andreas; Lee, Abraham P.; Wheeler, Aaron R.
Abstract : We check in with past, present, and future Editors-in-Chief, including Andreas Manz (2001–2008), Abe Lee (2017–2020), and Aaron Wheeler (2021–), about the state of the field.